Chemical Characterization, Leishmanicidal Activity and In Vitro Cytotoxicity of the Essential Oil Extracted from Pectis brevipedunculata (Gardner) Sch.Bip. and Its Incorporation into Microemulsion Systems - Auxiliadora Cristina Correa Barata Lopes; Jessyane Rodrigues do Nascimento; Marcos Bispo Pinheiro Camara; Aldilene da Silva Lima; Gláucia Laís Nunes Lopes; Matheus Oliveira do Nascimento; Júlia Karla Albuquerque Melo Xavier; Caroline Martins de Jesus; Cáritas de Jesus Silva Mendonça; André Luis Menezes Carvalho; Lucilene Amorim Silva; Cláudia Quintino da Rocha (MDPI AG, 2024)
Pectis brevipedunculata (Gardner) Sch.Bip., known in Brazil as alecrim do campo, is a small Asteraceae family plant with a calming effect and consumed as tea. This species contains components, such as neral and geranial, that display various biological activities, such as leishmanicidal. The aim was to chemically characterize the essential oil (EO) obtained from P. brevipedunculata (EO-PB) by hydrodistillation and a microemulsion formulated with EO (ME-PB), Tween 80 and Transcutol P, assess the leishmanicidal effect against Leishmania (L.) amazonensis promastigotes and cytotoxicity against RAW 264.7. EO-PB and ME-PB were analyzed by Gas Chromatography Mass Spectrometry (GC/MS). Monoterpene hydrocarbons were noteworthy among the identified compounds. The main EO-PB constituents were α-pinene and limonene, followed by neral and geranial, which were maintained in ME-PB. EO-PB presented an inhibitory concentration (IC50) of 20 µg/mL and ME-PB of 0.93 µg/mL. ME-PB inhibition towards the parasite was 20-fold higher than that of EO-PB. This indicated that EO incorporation to the microemulsion resulted in optimized biological activity. Selectivity indices indicate that ME-PB is more selective concerning parasite inhibition. Thus, ME-PB may comprise an adequate approach against Leishmania, as the inhibitory concentration (IC50) promastigotes was lower than that considered toxic for cells cell cytotoxicity of 50% (CC50).